A Review of Die Casting Methods in Manufacturing Processes - Sikumbang, Rama Widjaya; Pranoto, Hadi (Institute for Research on Innovation and Industrial System (IRIS), 2025)
This review explores seven die casting methods: High-Pressure Die Casting (HPDC), Low-Pressure Die Casting (LPDC), Vacuum Die Casting (VDC), Gravity Die Casting (GDC), Squeeze Casting, Semisolid Metal Casting (Thixomolding), and Cold Chamber Die Casting. Each method is evaluated based on its advantages, limitations, and industrial applications. HPDC is widely used for high-volume production but faces challenges like porosity and mold wear. LPDC offers better material density with slower production rates. VDC produces high-quality components with minimal defects but is more costly. GDC is suitable for simple geometries and smaller volumes, while Squeeze Casting delivers high strength and density, ideal for automotive parts. Thixomolding offers precise material flow, producing lightweight, strong components. Cold Chamber Die Casting is effective for high-melting metals but requires careful heat control. The review also discusses advancements in materials, mold designs, and simulation technologies, which enhance the efficiency and sustainability of die casting processes. Despite existing challenges, die casting remains a critical method for high-precision, large-scale manufacturing. Choosing the right method depends on product specifications and industry needs.